A Descriptive Study of Digital Stress among Employees Who Adopt a Hybrid Working System at PT.XYZ - Nadya Ganis Angesti; Audry Belda Azalia; Meidelinne Sebastian; Natasha Wijaya; Daniel Lie; Roland Bonggo Pribadi (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
One consequence of pandemic COVID-19 was that most companies implemented a hybrid working system (a mixture of work from home and office). During this period, employees at PT. XYZ who adopted the hybrid working system, experienced stress that caused by the usage of massive information and communication technology, that resulted in psychological detrimental effects. The objective of this study was to investigate the level and the types of digital stresses that faced by those employees. This research took place in March 2022, used a quantitative, online survey-based questionnaire named Digital Stressors Scale (α = 0.865) consisted of 50 questions with seven-points Likert Scale and convenient sampling technique, involving 107 employees of PT. XYZ as the participants. Data were then analyzed using descriptive statistics with the help of SPSS software. Result suggested that overall employees faced a high level of digital stress and the highest mean among the 10 dimensions of digital stress was invasion (M = 4.18, SD = 1.47 - stress about the tendency harming their individual personal data). The result is expected to help the management to think of various solutions to curb the problems as to improve the well-being of the employees working at PT. XYZ.